Implementasi CSR PT. Koninis Fajar Mineral di Kabupaten Banggai - Muhamad Ramdan; Ilyas; Febri Herawati (KOMUNIKA, 2026)
The presence of mining companies within local communities is never a simple matter. On one hand, these companies bring economic opportunities, yet on the other, they introduce tangible social and environmental risks. This is where Corporate Social Responsibility (CSR) programs should serve as a communication bridge between the company and the community. This study focuses on PT Koninis Fajar Mineral (KFM), which operates in Banggai Regency, to analyze the company's CSR communication strategy. A qualitative approach utilizing the case study method was employed. Data were gathered through in-depth interviews with company representatives, community leaders, and program beneficiaries, supplemented by field observations and document analysis. Data validity was ensured through source and method triangulation. Field findings reveal that while PT KFM has demonstrated intent and commitment regarding CSR, its communication strategy has not functioned effectively. Community needs assessment relies on incoming proposals rather than active field engagement. Some CSR programs remain administrative routines rather than responses to genuine needs. Communication largely relies on personal relationships and tends to be one-way. Program evaluation is virtually non-existent due to the lack of clear benchmarks and the absence of structured channels for community feedback. The study concludes that PT KFM’s CSR has not yet fully evolved into a strategic communication tool. The company needs to shift from a reactive approach toward communication that is genuinely two-way, planned, and consistently evaluable, thereby fostering an honest and sustainable relationship with the communities surrounding the mine.